Frame.io sebagai Web Service untuk Sistem Informasi Manajemen Film di Super 8mm Studio - Miqdad Miqdad; Wahyu Budi Priatna (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses the use of Frame.io as a web-based service in supporting the film management information system at Super 8mm Studio. The research focus is directed at improving the efficiency of post-production workflows and team collaboration through technology integration. The method used is a qualitative approach with case studies with the post-production team. The results show that the use of Frame.io is able to speed up the review process, facilitate file distribution, and increase transparency in the management of film projects. The Frame.io integration has a positive impact on the film production management information system at Super 8mm Studio. The platform not only simplifies technical processes such as video uploads and reviews, but also establishes a more open, responsive, and collaborative work culture. This improvement is especially important in the context of the creative industry that requires high adaptability and fast communication. Furthermore, the results of this study support the argument that the use of cloud-based digital platforms can be a strategic solution for independent production houses that want to improve their work efficiency and quality of production output without adding to the burden of high infrastructure costs.